2006
DOI: 10.1158/1055-9965.epi-05-0562
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of DNA Damage in WBCs of Workers Occupationally Exposed to Fumes and Aerosols of Bitumen

Abstract: We conducted a cross-shift study with 66 bitumen-exposed mastic asphalt workers and 49 construction workers without exposure to bitumen. Exposure was assessed using personal monitoring of airborne bitumen exposure, urinary 1-hydroxypyrene (1-OHP), and the sum of 1-, 2 + 9 -,3-,4-hydroxyphenanthrene (OHPH). Genotoxic effects in WBC were determined with nonspecific DNA adduct levels of 8-oxo-7, 8-dihydro-2V-deoxyguanosine (8-oxodGuo) and the formation of DNA strand breaks and alkali-labile sites. Concentration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 51 publications
1
21
1
Order By: Relevance
“…But a few conflicting results were reported (55) and critical comments were added from the methodologic point of view (56). Concentrations of 8-oxodGuo in this study were found to be higher than in construction and bitumenexposed workers, when measured with the same method and in the same laboratory (57). However, we could not find an association between 8-oxodGuo in WBC and any measure of exposure at the level of individual data in highly PAH-exposed workers.…”
Section: Discussioncontrasting
confidence: 71%
“…But a few conflicting results were reported (55) and critical comments were added from the methodologic point of view (56). Concentrations of 8-oxodGuo in this study were found to be higher than in construction and bitumenexposed workers, when measured with the same method and in the same laboratory (57). However, we could not find an association between 8-oxodGuo in WBC and any measure of exposure at the level of individual data in highly PAH-exposed workers.…”
Section: Discussioncontrasting
confidence: 71%
“…As shown in Fig. 2B, the urinary 8-oxodG at the end of work week had relatively lower levels compared with the other working days, probably because the biomarker of effect (e.g., 8-oxodG) may not only reflect the exposure during a week-shift but also a much longer period of exposure (43). Subsequently, the absence of significant correlation between 1-OHP and 8-oxodG in published studies could be also explained by that, in addition to polycyclic aromatic hydrocarbons, coke oven emissions also contain a variety of nitrosamines, coal tar, metal compounds, and so forth.…”
Section: Discussionmentioning
confidence: 93%
“…1,[4][5][6] Additionally, asphalt workers are exposed to emissions from the exhaust of passing vehicles. 4,[7][8][9] Respiratory effects of exposure to asphalt fume have been evaluated in a few studies. 5 However, conclusive results have not been obtained yet.…”
Section: A R T I C L Ementioning
confidence: 99%
“…5 The respiratory effects of asphalt fumes have so far been studied in a few countries such as USA, 10,12,16 , Germany, 7 and Norway. 1,4 However, for differences in the chemical structure and composition of asphalt concrete mixtures, the concentration of asphalt fumes to which workers were exposed, air temperature, mechanical rather than manual processing of asphalt, good occupational health practices in these countries and many other differences, the results of these studies are not necessarily comparable with those of other studies.…”
Section: A R T I C L Ementioning
confidence: 99%